Family Health Monitoring System Based on the Four Sessions Internet of Things - Yang Jingjing; Hao Shangfu; Zhang Xiao; Guo Benzhen; Liu Yu; Dong Beibei; Liu Yun (Universitas Ahmad Dahlan, 2015)
The accelerating pace of modern life results in the lack of effective care of people’s health status. Nowadays, resorting to the technology of the Internet of Things, we can provide home health monitoring services to minimize the impact of the disease brought to people. In this article, we proposed the realization method for the architecture of the four sections of the Internet of Things oriented to home health monitoring service, furthermore, the secondary the smoothness index method is applied to the monitoring of human health index, data from body temperature detection experiments verified the feasibility of the four sessions system, which laid firm foundations for the requirement of real-time and accuracy of the Internet of Things based home health monitoring system with a common reference significance and value in use.